BNIP3 as a progression marker in primary human breast cancer; opposing functions in in situ versus invasive cancer - Tan, Ern Yu; Campo, Leticia; Han, Cheng; Turley, Helen; Pezzella, Francesco; Gatter, Kevin C; Harris, Adrian L; Fox, Stephen B (Clinical cancer research, 2007)
BNIP3 is involved in cell death and cell survival via autophagy. Its perinecrotic localization within ductal carcinoma in situ (DCIS) suggests an involvement in neoplastic cellular adaptation to low oxygen tension. This study has investigated the role of BNIP3 in normal and neoplastic breast. Whole sections from 11 normal breast and microarrayed tissue cores from 81 DCIS and 251 invasive carcinomas were stained for BNIP3 and hypoxia-inducible factor-1alpha. The pattern and level of BNIP3 expression were correlated with clinicopathologic variables and hypoxia-inducible factor-1alpha. BNIP3 expression was significantly up-regulated in the cytoplasm of DCIS and invasive carcinoma compared with normal breast (P = 0.0005 and P < 0.0001, respectively). Nuclear BNIP3 expression was associated with smaller tumor size (P = 0.04), low tumor grade (P = 0.005), and estrogen receptor positivity (P = 0.008) in invasive tumors. Nuclear BNIP3 expression was also associated with a longer disease-free survival among low-grade and estrogen receptor-positive tumors. (P = 0.03 and 0.04, respectively). Conversely, nuclear BNIP3 expression in DCIS was associated with a 3-fold increase in recurrence and a shorter disease-free survival (P = 0.03). Up-regulation of BNIP3 expression in DCIS and invasive carcinoma suggests a significant role in breast tumor progression. Its association with good survival outcome in invasive carcinoma but with an increased risk of recurrence and shorter disease-free survival in DCIS may suggest a pivotal switch from a cell death to survival function during the transition from preinvasive to invasive breast cancer.